Implementasi Model Project Based Learning dalam Meningkatkan Motivasi Belajar Siswa pada Pembelajaran PAI - Nadya Azzahra; Asep Tutun Usman; Iman Saifullah (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2026)
This study aims to describe the implementation of the Project-Based Learning (PjBL) model and to analyze the improvement of students’ learning motivation in Islamic Religious Education (IRE) learning at SD GIS Prima Insani. This research employed a qualitative approach with a descriptive research design. The research subjects consisted of an IRE teacher and students of class VI-A. Data were collected through observation, interviews, and documentation, while data analysis was conducted using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The results indicate that the implementation of PjBL was carried out systematically through the stages of planning, project implementation, monitoring, presentation, and evaluation. The application of PjBL through a picture story (comic) project on the topic of the Prophet Muhammad’s mission and his da’wah strategies in Mecca was able to enhance students’ learning motivation. The improvement in learning motivation was reflected in several indicators, including persistence, interest and attention, active participation, independence, responsibility, goal orientation, and students’ self-confidence. In addition, the improvement in cognitive learning outcomes was positioned as an indirect impact of the increased learning motivation following the implementation of PjBL. Therefore, the Project-Based Learning model can be considered an effective alternative instructional strategy to enhance students’ learning motivation in Islamic Religious Education at the elementary school level.